The Relationship Between Nurses’ Digital Health Literacy and Emotional Exhaustion in Tertiary Care Hospitals - Noor, Aisha (International Journal of Health Sciences, 2026)
Purpose: The purpose of this article was to analyze the relationship between nurses' digital health literacy and emotional exhaustion in tertiary care hospitals. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Based on current research, a significant inverse relationship exists between nurses' digital health literacy and emotional exhaustion in tertiary care hospitals. Higher proficiency in using digital health tools and navigating electronic health information is consistently associated with lower levels of emotional exhaustion, a core dimension of burnout. This suggests that improving digital health literacy may serve as a protective factor, enhancing work efficiency and reducing the technological stress that contributes to burnout among nurses in high-complexity care settings. Unique Contribution to Theory, Practice and Policy: Job demands-resources (JD-R) theory, transactional model of stress and coping conservation of resources (COR) theory may be used to anchor future studies on the relationship between nurses' digital health literacy and emotional exhaustion in tertiary care hospitals. For hospital administrators and nurse leaders, this study provides actionable, evidence-based strategies to mitigate burnout by targeting a modifiable skill set. At the policy level, this research provides a compelling evidence base to advocate for systemic changes that protect the nursing workforce in an increasingly digital healthcare ecosystem.